Comparison of bubbles interaction mechanisms of two-group Interfacial Area Transport Equation model. (June 2023) - Kuidjo, E.V. Kuidjo; Rodio, M.G.; Abgrall, R.; Sagaut, P.
Abstract: This work deals with 3D simulations of complex bubbly, cap-bubbly and churn regimes exhibiting bubbles of different shapes and with broad bubble size distribution. The first contribution of this work is to investigate and compare several bubble interaction mechanisms of coalescence and fragmentation for the 2-Group Interfacial Area Transport Equation (IATE) model. For two of these models, this is the first time their performances are assessed within a CFD code. The second contribution is to propose and assess a novel model of fragmentation and coalescence. Finally, a validation versus experimental data on three different configurations and three different regimes is performed. In particular, the interaction mechanisms are analysed for one specific regime. The implementation of the two-group IATE model has been systematically performed in the 3D NEPTUNE CFD code. Highlights: Comparison of four Coalescence/Break-up (C/B) models implemented in a CFD code. Proposition of a novel C/B model and its validation. Validation on three different configurations: confined rectangular section, small and a large diameter pipe. Three regimes investigated: bubbly, cap-turbulent and churn.